Behavioral nutrition applied to the treatment of obesity - de Araújo , Chiara Salustri; Rocha, Edenilda Rita Pereira; Castro , Giovanna Palomo; Barbosa , Karine Oliveira Reder; Flores , Nicolle de Souza; Masquio, Déborah Landi (Seven Editora, 2023)
Obesity is a chronic disease, difficult to control. Even with traditional treatments, such as diet prescription, physical exercise, psychological and drug therapy, the obesity prevalence still continues to increase in worldwide. Thus, behavioral nutrition emerges as a possibility in the control of this disease. This study aimed to understand the role of behavioral nutrition in the treatment of obesity. This is a literature review, conducted through online research in Pubmed, Scielo and Lilacs. Publications from the last ten years in Portuguese and English were included. Reference books in the area were also consulted. The keywords used in the search were: obesity, feeding behavior, mildfulness eating, and intuitive eating. The Boolean AND and OR techniques were used to combine the keywords. Behavioral nutrition is a psychological method, which aims to understand food as a whole, and its main objective is to change negative relationships with food. Thus, the application of behavioral nutrition in obesity treatment can favor the individual to see food as a source of both nutrition and pleasure, but not as an "enemy". It is known that obesity is directly associated with eating-related behavior patterns and changes of satiety recognition. In this sense, behavioral nutrition techniques broaden the range of interventionist possibilities to rescue the recognition of the hunger and satiety cycle and the factors that interferes in this process. Strategies of behavioral nutrition applied in the treatment of obesity include nutritional counseling, intuitive eating, cognitive-behavioral therapy, motivational interviewing, and mindful eating tactics. It is concluded that the application of behavioral nutrition promotes recognition of hunger and satiety signals, and may generate even greater benefits in the treatment of obesity. DOI:https://doi.org/10.56238/ptoketheeducati-061